MEMPERKUAT NALAR TEOLOGI ISLAM MODERAT DALAM MENYIKAPI PANDEMI COVID-19 DI PIMPINAN RANTING PEMUDA MUHAMMADIYAH BANDAR PULAU PEKAN - Ginting, Nurman; Pradesyah, Riyan; Amini, Amini; Panggabean, Hadi Sahputra (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Religion for some people in the world is a guideline for determining the direction to be directed in their life. In life in this world, the most important thing is a peace of mind and body in society. In keeping up with the current changes, a good reasoning process is urgently needed as a solution to addressing this to break the chain of the spread of the Covid-19 outbreak. Moderate Islam is a teaching that is able to keep up with the times and does not abandon the teachings afterwards. So that Moderate Islam is a religion that is able to balance the movement of changes in life in society. The understanding of moderate Islamic values is currently being eroded by the changing times, so that many young people tend to be pragmatic, exclusive and intolerant in responding to the situation and conditions of the Covid-19 pandemic which is spreading so rapidly today.